Rapidly progressing dementia as a manifestation of the Creutzfeldt-Jakob disease: an analysis of two cases - Bartosz, Seweryn; Leksa, Natalia; Uberman-Kluz, Dominika; Szymczak, Artur; Biesiadecki, Marek; Galiniak, Sabina (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Creutzfeldt-Jakob disease (CJD) is a rare and fatal neurodegenerative disease of the central nervous system which is caused by an infectious protein called prion. Multiple forms of CJD have been classified including sporadic (more than 90% cases), familial, iatrogenic and variant type of disease. CJD, especially in its early stages, is a highly challenging illness to diagnose. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Article aims to present cases of Creutzfeldt-Jackob disease with early symptoms of rapidly progressing dementia at the initial stage of CJD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the cases. This paper describes two cases of patients with suspected CJD with a history of rapidly progressive dementia admitted to the Department of Neurology, MSWiA Hospital in Rzeszów. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Despite the fact that CJD is an incurable illness and there is no cure guaranteeing recovery, it is important to make the right diagnosis. Assay of 14-3-3 protein in cerebrospinal fluid is a sensitive and specific marker which is helpful in the diagnosis of CJD. The only relevant method of correctly confirming a diagnosis of this disease is by performing a brain biopsy.